2019
DOI: 10.1038/s41598-019-53060-1
|View full text |Cite
|
Sign up to set email alerts
|

Limnological effects of a large Amazonian run-of-river dam on the main river and drowned tributary valleys

Abstract: Run-of-river dams are often considered to have lower environmental impacts than storage dams due to their smaller reservoirs and low potential for flow alteration. However, this has been questioned for projects recently built on large rivers around the world. Two of the world’s largest run-of-river dams—Santo Antônio and Jirau—were recently constructed on the Madeira River, a major tributary to the Amazon River in Brazil. Here we evaluate the effects of the creation of the Santo Antônio dam on the water chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 41 publications
2
20
1
Order By: Relevance
“…A remote sensing analysis has revealed that the area inundated by the Jirau and Santo Antônio dams is 60% larger than initially predicted in pre-dam environmental impact assessments (Cochrane et al, 2017), which may be in part related to changes in project design. Although the residence time of the Madeira dams is short (Figure 1), drowned tributary valleys created by the dams show significant limnological alterations, including thermal stratification and increased availability of organic matter (De Faria et al, 2015;Almeida et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…A remote sensing analysis has revealed that the area inundated by the Jirau and Santo Antônio dams is 60% larger than initially predicted in pre-dam environmental impact assessments (Cochrane et al, 2017), which may be in part related to changes in project design. Although the residence time of the Madeira dams is short (Figure 1), drowned tributary valleys created by the dams show significant limnological alterations, including thermal stratification and increased availability of organic matter (De Faria et al, 2015;Almeida et al, 2019a).…”
Section: Introductionmentioning
confidence: 99%
“…Wind and drifting speed do not show grouping statistics because of the small number of measurements, and consequently, not meeting assumptions requirements for the statistical test. potentially mixed water column in the reservoir's main channel, indicated by a homogeneous temperature profile in a location in the main channel of the reservoir near Site 1 (Almeida et al, 2019a), could sustain oxygen levels in the water at the bottom and help exchange O 2 from the water into the sediment surface, potentially increasing sediment CH 4 oxidation at the sediment water interface.…”
Section: Internal and Local Variabilitymentioning
confidence: 99%
“…Although this study was focused on the reservoir's main channel, it is important to highlight that the large drowned areas, especially in tributary valleys, can develop lake-like conditions and water column stratification (Almeida et al, 2019a). The higher water residence time in these areas allows sedimentation of fine organic sediments and may create oxygen stratification that favors CH 4 accumulation in the hypolimnion.…”
Section: Internal and Local Variabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In view of the comprehensive ecological effects of lake-river interaction, lake water retention has received more concerns in floodplain regions [6,7]. Water residence time mainly focuses on reservoirs or run-of-river dams [8]. Hydrological regimes of lake and river are extensively altered by damming and water diversion [9,10], as an enlarged channel storage lake plays an important role in alleviating flood and maintaining wetland ecology [11,12].…”
Section: Introductionmentioning
confidence: 99%